Intra-aortic balloon pump protects against hydrostatic pulmonary oedema during peripheral venoarterial-extracorporeal membrane oxygenation. Issue 1 (1st February 2018) - Bréchot, Nicolas; Demondion, Pierre; Santi, Francesca; Lebreton, Guillaume; Pham, Tai; Dalakidis, Apostolos; Gambotti, Laetitia; Luyt, Charles-Edouard; Schmidt, Matthieu; Hekimian, Guillaume; Cluzel, Philippe; Chastre, Jean; et al.
Abstract: Background: Increased left ventricular afterload during peripheral venoarterial-extracorporeal membrane oxygenation (VA-ECMO) support frequently causes hydrostatic pulmonary oedema. Because physiological studies demonstrated left ventricular afterload decrease during VA-ECMO assistance combined with the intra-aortic balloon pump (IABP), we progressively changed our standard practice systematically to associate an IABP with VA-ECMO. This study aimed to evaluate IABP efficacy in preventing pulmonary oedema in VA-ECMO-assisted patients. Methods: A retrospective single-centre study. Results: Among 259 VA-ECMO patients included, 104 received IABP. Weinberg radiological score-assessed pulmonary oedema was significantly lower in IABP + than IABP – patients at all times after ECMO implantation. This protection against pulmonary oedema persisted when death and switching to central ECMO were used as competing risks (subhazard ratio 0.49, 95% confidence interval (CI) 0.33–0.75; P <0.001). Multivariable analysis retained IABP as being independently associated with a lower risk of radiological pulmonary oedema (odds ratio (OR) 0.4, 95% CI 0.2–0.7; P =0.001) and a trend towards lower mortality (OR 0.54, 95% CI 0.29–1.01; P =0.06). Finally, the time on ECMO free from mechanical ventilation increased in IABP + patients (2.2±4.3 vs. 0.7±2.0 days; P =0.0003). Less frequent pulmonary oedema and more days off mechanical ventilation were also confirmed in 126 highly comparable IABP + and IABP – patients, propensity score matched for receiving an IABP. Conclusions: Associating an IABP with peripheral VA-ECMO was independently associated with a lower frequency of hydrostatic pulmonary oedema and more days off mechanical ventilation under ECMO.